FACTORS THAT AFFECTING REVALUATION OF FIXED ASSETS IN MANUFACTURING COMPANIES - Salsabil, Nurul Hana'; Alliyah, Siti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research aims to prove the influence of fixed asset intensity, leverage, and company size on the revaluation of fixed assets in manufacturing companies listed on the IDX for the 2020-2022 period. Documentation techniques were used to collect data in this research, while a purposive sampling approach was used for sampling to produce samples that met the research requirements. The research sample consisted of 145 companies with a total of 435 observations. In this research, the SPSS program was used to test logistic data regression analysis techniques. The results of this research show that fixed asset intensity and company size have a positive and significant effect on fixed asset revaluation, while leverage has an insignificant positive effect on fixed asset revaluation. The results of this study have implications in helping fixed asset revaluation researchers in determining gaps and novelties for further research and can provide information for users of financial reports related to these factors influencing companies to the revaluation of fixed assets.